1993
DOI: 10.1029/93jb00694
|View full text |Cite
|
Sign up to set email alerts
|

A generalization of the demagnetizing tensor for nonuniform magnetization

Abstract: The demagnetizing tensor for ferromagnets is generalized to include interactions between uniformly magnetized bodies. This “mutual” demagnetizing tensor is symmetric, has a trace of zero, and has other simple geometric properties. The tensor is then used to develop an expression for the macroscopic magnetic field in non‐uniformly magnetized bodies of arbitrary shape. Finally, the theory is applied to a block model of magnetization and explicit formulae for the tensor components are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
174
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(179 citation statements)
references
References 17 publications
1
174
2
2
Order By: Relevance
“…Indeed, the FL magnetization is expected to be more non-uniform -and consequently easier to switchin the low-field P state because of the mutual dipolar coupling field pointing antiparallel to the magnetizations in the P state, but parallel in the AP state. Within the diagonal tensor approximation of the mutual dipolar coupling, the tensor components are found to be significantly smaller than the values predicted by the formalism developed by Newell et al 21 or by the simplified version using for the in-plane components of the mutual dipolar coupling tensor the corresponding components of the self-demagnetizing tensor, as is commonly practiced when modeling flip-flop switching in MRAM cells. 36,37 The coupling between e.g.…”
Section: A Materials and Geometry Parametersmentioning
confidence: 67%
See 4 more Smart Citations
“…Indeed, the FL magnetization is expected to be more non-uniform -and consequently easier to switchin the low-field P state because of the mutual dipolar coupling field pointing antiparallel to the magnetizations in the P state, but parallel in the AP state. Within the diagonal tensor approximation of the mutual dipolar coupling, the tensor components are found to be significantly smaller than the values predicted by the formalism developed by Newell et al 21 or by the simplified version using for the in-plane components of the mutual dipolar coupling tensor the corresponding components of the self-demagnetizing tensor, as is commonly practiced when modeling flip-flop switching in MRAM cells. 36,37 The coupling between e.g.…”
Section: A Materials and Geometry Parametersmentioning
confidence: 67%
“…Using the formulae in Ref. 21 it can be shown that the dipolar coupling constants obey similar relations, N y ml /N x ml = L x /L y and N z ml = −(N x ml + N y ml ), and for symmetry reasons, N ml = N lm . The remaining components N x F 1 , N x F 2 , and N x 12 are kept as free parameters to be extracted from the experiment, although they can be calculated by means of Ref.…”
Section: Reduction Of Number Of Free Parametersmentioning
confidence: 93%
See 3 more Smart Citations